International validation of the Bullous Pemphigoid Disease Area Index severity score and calculation of cut‐off values for defining mild, moderate and severe types of bullous pemphigoid*. (1st June 2021) - Masmoudi, W.; Vaillant, M.; Vassileva, S.; Patsatsi, A.; Quereux, G.; Moltrasio, C.; Abasq, C.; Prost‐Squarcioni, C.; Kottler, D.; Kiritsi, D.; Litrowski, N.; Plantin, P.; et al.
Summary: Background: The Bullous Pemphigoid Disease Area Index (BPDAI) score has been proposed to provide an objective measure of bullous pemphigoid (BP) activity. Objectives: The objective of this study was to calculate BPDAI cut‐off values defining mild, moderate and severe BP. We also aimed to assess the interrater reliability and correlation with the number of daily new blisters, and anti‐BP180 and anti‐BP230 antibodies. Methods: Severity scores were recorded by two blinded investigators. Anti‐BP180 and anti‐BP230 antibodies were measured using an enzyme‐linked immunosorbent assay (ELISA). Cut‐off values defining mild, moderate and severe subgroups were calculated based on the 25th and 75th percentiles of the BPDAI score. Results: In total, 285 patients with BP were enrolled from 50 dermatology departments in Europe. Median BPDAI activity was 37·5 points (range 0–164). Cut‐off values corresponding to the first and third quartiles of the BPDAI score were 20 and 57, respectively; thus, these values were used to define mild (≤ 19), moderate (≥ 20 and ≤ 56) and severe (≥ 57) BP. The median BPDAI score for patients with ≤ 10 daily new blisters was 26 [interquartile range (IQR) 17–45], and for patients with > 10 daily new blisters the median score was 55 (IQR 39–82). The BPDAI intraclass correlation coefficient measured at baseline was 0·97 and remained higher than 0·90 up to month 6. The improvement in the BPDAI score was correlated with the absolute decrease in anti‐BP180 ELISA value (Spearman's rank r  = 0·34, P  < 0·004), but not with anti‐BP230 antibodies ( r  = 0·17, P  = 0·15). Conclusions: This study suggests cut‐off values of 20–57 for BPDAI to distinguish mild, moderate and severe BP, and confirms that it is a robust tool to assess BP severity precisely. Abstract: What is already known about this topic? The Bullous Pemphigoid Disease Area Index (BPDAI) is a new scoring system to measure bullous pemphigoid (BP) activity. The use of this score in clinical practice is limited by the absence of cut‐off values. What does this study add? Cut‐off values of 20 and 57 were established to distinguish mild, moderate and severe BP using the BPDAI. These disease activity subgroups could help physicians in the management of patients with BP. What are the clinical implications of this work? This study classified patients with BP into three subgroups (mild, moderate and severe) based on the BPDAI score. The BPDAI score is a robust tool to assess BP activity accurately, both at diagnosis and during the course of the disease, and could help physicians tailor treatment to disease activity, thereby providing better management of patients with BP. Linked Comment:  Blome and Klein. Br J Dermatol 2021; 184 :997–998 .